Effects of ameliorative afforestation on the erodibility factor and soil loss in the Grdelica gorge - Aleksandar Baumgertel; Sara Lukić; Snežana Belanović Simić; Predrag Miljković (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The paper presents research carried out in the area of Grdelica gorge in 60 years old black pine (Pinus nigra Arnold.) stands. The aim of this study was to determine whether the applied planting method of ameliorative afforestation had an impact on physical and chemical soil properties, soil erodibility and soil loss. The experimental fields were selected from the afforested areas where soil samples were taken from fixed depths and then were subjected to physical and chemical laboratory analyses. The soil erodibility factor K was calculated using the Wischmeier and Smith formula, whilst, soil loss was estimated according to Erosion Potential method – EPM by Gavrilović. According to the results of the research, in the studied period of 60 years there was a change in the soil physical and chemical properties. There was also a reduction in the soil erodibility factor and soil loss which can be the result of ameliorative afforestation. The afforestation method can affect the reduction of soil losses, while the erodibility factor may be affected indirectly (e.g. by increase in the organic matter content, forming structural aggregates) not immediately after afforestation, but in a long term period.